The Rhetorical Analysis of the Style of Aqqad in his Book Sareh - Mahmood Khorsandi; Mohammad Khaqani Isfahani; Ali Zeighami; Vajiheh Sadat sayyed Bokaei (دراسات فی اللغه العربیه و آدابها)
A literary work can be appraised for its style in different ways. This study intends to investigate the intellectual aspects of Sareh by Mahmood Aqqad. This book shares some aspects with other plays and novels, but enjoys distinctive characteristics such as the use of rhetorical devices for textual and discourse purposes, different dimension, of discourse analysis tools, using popular stories, and employing sincere and tangible figurative language. The present article investigates this book for different textual dimensions such as style, discourse and rhetorical devices, so that it is proved that Aqqad's style can be described from a discoursal and rhetorical stance and logical and rational strands are stronger than imaginative ones. This claim can be elaborated according to the characteristics and evidence in the book.